Digital games and journalism - Vobič, Igor (Teorija in praksa, 2014)
By taking the cultural approach to converging journalism-games dynamics, the study aims to investigate how games can be used beyond entertainment as means to depict recent events, serve as commentaries and realise other editorial pursuits. The case study investigates the Slovenian political weekly Mladina and its Tetris-style newsgame Fojba 2000 by conducting procedural rhetoric analysis and in-depth interviews with Mladina editors, journalists and game developers. The analysis indicates patterns of coordinated cross-company production, the polysemous character of the newsgame as a form of communication, and various perceptions of its societal relevance inside and outside the Mladina newsroom.
Keywords: Časniki; Fojba 2000; Journalism; Mladina (periodična publikacija); Newspapers; Novinarstvo; Slovenia; Slovenija; Video games; Videoigre